Stereotactic Radiosurgery in Recurrent Brain Metastases After Prior Radiosurgery: A Case Report and Review of Literature - HENRY KODRAT; RIMA NOVIRIANTHY (Indonesian Journal of Cancer, 2016)
ABSTRACTPreviously, all brain metastasis has been treated with whole brain radiotherapy and the survival is poor. Recently, the development of stereotactic radiosurgery (SRS) provides comparable efficacy with low toxicity, and in several cases have a better survival compared to historical data. We conducted a case review in brain metastasis, which has been treated with SRS previously and experienced distant brain recurrence, then re-treated with SRS.ABSTRAKDahulu, semua metastasis otak ditangani dengan modalitas radiasi seluruh otak dan memiliki kesintasan yang tidak terlalu baik. Saat ini berkembang modalitas stereotactic radiosurgery (SRS). SRS memberikan efektivitas yang sebanding dengan toksisitas yang rendah dan pada beberapa kasus memiliki kesintasan yang lebih baik dibandingkandata sebelumnya. Berikut adalah tinjauan kasus metastasis otak dengan penanganan SRS sebelumnya dan mengalami kekambuhan di lokasi lain pada otak, kemudian ditatalaksana ulang dengan SRS.